Sensitivity analysis in shape optimization design for pressure vessel - 433696 Kang, Chang Wei (Skudai : Universiti Teknologi Malaysia, 2002)
Project Paper (Bachelor of Engineering (Mechanical) - University Teknologi Malaysia, 2002